That's like me! : stories about amazing people with learning differences - Lauren, Jill, 1961- (Star Bright Books, 2009)
What do a trapeze artist, an Arctic explorer, and a soccer player have in common? Meet the fifteen kids and adults profiled in "That's Like Me!," a collection of first-person accounts of successful people who learn differently. Whether it was reading, math, writing, or speech problems, each person shares his or her inspiring story of facing the challenge of school, while pursuing important goals.